KOMPOSISI DAN KEANEKARAGAMAN JENIS TUMBUHAN GOLONGAN POHON DI KAWASAN HUTAN LINDUNG NANGA-NANGA PAPALIA KOTA KENDARI SULAWESI TENGGARA - Muhsin, Muhsin; Indrawati1, Indrawati; Rahardi, Wira (Jurnal BioWallacea, 2015)
The aim of this research was to know the composition, diversity and distribution ofdiameter class (vertical structures) of plant on tree categories in Protected Forest Area ofNanga-Nanga Papalia, Kendari Town, Southeast Sulawesi Province. This research wasdone by using 5 terraced transects, which was laid followed the river stream by consideringthe elevation place and vegetated condition. Each transect consist of 5 observed plots whichwere laid systematically along the transect line. Variables observed was the composition anddiversity of plant species by the growth stager including tree, pole, sapling, seedling andstand diameter. Ecological indicators of plants were analysed including number of species,density, relative density, frequency, relative frequency, dominancy, relative dominancy,important value index, diversity index, evennes index and stand diameter. The result showedthat were discovered about 53 species of plants on tree categories, which were classifiedinto 27 families and were distributed by the growth stager, i.e. 31 species of tree, 42 speciesof pole, 31 species of sapling and 26 species of seedling. Metrosideros petiolata had thehighest important value index for the growth stager tree and pole (54,474% and 62, 516%),while Baringtonia racemosa had the highest important value index for growth stager saplingand seedling (36,361% and 31,504%). The diversity index was in estimated grade for treeand seedling (2,908 and 2,529), while the diversity index was in high grade for pole andsapling (3,102 and 3,032). The distribution of stand diameter of plants in Protected ForestArea of Nanga-Nanga Papalia showed a balanced community which was dominated bytrees.Key words : Stand Diameter, Tree Categories, Protected Forest Area, Diversity,Composition.